Peran Konsultan Keuangan dalam Meningkatkan Kualitas Pengambilan Keputusan Manajemen Berbasis Prinsip Islam - Hilman Lubis (JURNAL SYIAR-SYIAR, 2024)
This study aims to explore the role of financial consultants in improving the quality of management decision-making through the application of Islamic principles. The study employs a literature review method to identify the challenges and benefits faced in implementing Islamic principles by financial consultants. The findings reveal that the primary challenges include the lack of adequate legal frameworks, a shortage of trained human resources, Shariah non-compliance risks, and the complexities of technological integration. However, the study also identifies significant benefits, such as the promotion of ethical and sustainable finance, market differentiation, regulatory support, and positive social impacts through financial inclusion. The conclusion emphasizes that despite the barriers to implementation, the benefits of adopting Islamic principles by financial consultants are highly valuable. This adoption not only enhances the quality of decision-making but also supports organizational sustainability, community welfare, and ethical integrity in the modern financial world.